FACTORS ASSOCIATED WITH EXCLUSIVE BREASTFEEDING IN INDONESIA: A QUALITATIVE STUDY AMONG WORKING MOTHERS - Syafiq, Ahmad; Avianty, Selma; Fikawati, Sandra; Japri, Andrew Prasettya; Septiani, Seala; Basrowi, Ray Wagiu (Journal of Indonesian Specialized Nutrition, 2025)
Exclusive breastfeeding (EBF) is a globally recommended practice, yet its proportion remains low in Indonesia, particularly among working mothers. Various factors, including workplace policies, socioeconomic status, and family support, influence EBF success. This study aims to explore the supporting and inhibiting factors of EBF among working mothers in urban and semi-urban areas in Indonesia. A qualitative study was conducted through in-depth interviews to 14 working mothers with children aged 6–24 months in Jakarta (urban) and Beji-Depok (semi-urban) between October 2016 and January 2017. Participants were selected using purposive and snowball sampling, considering variations in breastfeeding status, occupation, and dwelling location. Data were analyzed through thematic content analysis with expert triangulation. Key factors influencing EBF included postpartum health, maternity leave policies, socioeconomic conditions, family and external support, and access to EBF-related information. White-collar mothers faced workplace-related barriers but benefited from strong internal and external support. Blue-collar mothers, constrained by economic factors, showed higher EBF adherence due to lacked comprehensive EBF knowledge. Health workerrecommendations influenced breastfeeding decisions. Enhancing workplace support, strengthening family engagement, and improving targeted education for working mothers are crucial to increasing EBF adherence. Further research involving healthcare providers is recommended.